Controversial issues in the management of patients with advanced prostate cancer: Results from a Canadian consensus forum - Saad, Fred (Can Urol Assoc J, 2020)
INTRODUCTION: The management of advanced prostate cancer (PCa) continues to evolve with the emergence of new diagnostic and therapeutic strategies. As a result, there are multiple areas in this landscape with a lack of high-level evidence to guide practice. Consensus initiatives are an approach to establishing practice guidance in areas where evidence is unclear. We conducted a Canadian-based consensus forum to address key controversial areas in the management of advanced PCa. METHODS: As part of a modified Delphi process, a core scientific group of PCa physicians (n=8) identified controversial areas for discussion and developed an initial set of questions, which were then reviewed and finalized with a larger group of 29 multidisciplinary PCa specialists. The main areas of focus were non-metastatic castration-resistant prostate cancer (nmCRPC), metastatic castration-sensitive prostate cancer (mCSPC), metastatic castration-resistant prostate cancer (mCRPC), oligometastatic prostate cancer, genetic testing in prostate cancer, and imaging in advanced prostate cancer. The predetermined threshold for consensus was set at 74% (agreement from 20 of 27 participating physicians). RESULTS: Consensus participants included uro-oncologists (n=13), medical oncologists (n=10), and radiation oncologists (n=4). Of the 64 questions, consensus was reached in 30 questions (n=5 unanimously). Consensus was more common for questions related to biochemical recurrence, sequencing of therapies, and mCRPC. CONCLUSIONS: A Canadian consensus forum in PCa identified areas of agreement in nearly 50% of questions discussed. Areas of variability may represent opportunities for further research, education, and sharing of best practices. These findings reinforce the value of multidisciplinary consensus initiatives to optimize patient care.